A fuzzy GPSR route selection based on link quality and neighbor node in VANET - Aljabry, Israa A.; Al-Suhail, Ghaida A.; Abdullah, Waheb Abdul Jabbar Shaif (Institute of Electrical and Electronics Engineers Inc., 2021)
Over recent years, a new technology named VANET (Vehicular Ad-hoc Networks) is highly recommended in smart cities and especially in Intelligent Transportation Systems (ITS). The VANET technology relies on the nodes acting like cars without the necessity for any controller or central base station by creating a wireless link among them. It enables cars to send and receive information between themselves and their environment. most VANETs utilize position-based routing protocols because they contain a GPS device. To deal with VANET problems, one solution is Geographic Perimeter Stateless Routing (GPSR) which has been broadly implemented. This paper suggests an effective intelligent fuzzy logic control system; called the FL-QN GPSR routing protocol. The proposed routing protocol incorporates two metrics link quality, and neighbor node to detect the best next-hop node for packet forwarding also updates the format of the Hello message by adding the direction field to be more suitable to our simulation. The OMNeT++ and SUMO simulation tools are both used in parallel to examine the VANET environment. The obtained results of the four simulation experiments in urban environments indicate substantial improvements in the network performance compared to the traditional GPSR and AODV concerning the QoS parameters.